Teaching Learning Process Assessment based on Students Evaluation - S. , Vijaya; L. , Padmavathy; P. , Lavanya; T. , Prabha (International Journal of Psychosocial Rehabilitation, 2020)
In the past two decades, teaching in higher education has risen in status and given much importance, especially in improving teaching and learning methodology from the evaluation of teachers done by students. Different parameters of teaching methods of faculties are taken into account and evaluated through students to find out the best teaching methodology. As feedback is given from the consumer’s point of view, most importantly, students’ evaluation reports provide faculties with important feedback.